Diagnosis of maternal and child health situation in the municipality of Tanque do Piauí-PI - Lorena Sousa Soares; Sylvia Leite Bento; Grazielle Roberta Freitas da Silva (Universidade de Fortaleza, 2013)
Objective: To describe the diagnosis of maternal and child health in the city of Tanque do Piauí-PI. Methods: This is a cross-sectional, descriptive study using epidemiological survey by downloading the database for the years of 2007, 2008 and 2009 from the Ministry of Health official systems. The variables analyzed were: demographic and socioeconomic indicators; mortality; morbidity and risk factors; resource and coverage; and SISPRENATAL indicators. Results: With the results, the main epidemiological measures for the municipality were observed, especially regarding maternal and child health situation. It was noted a situation of social vulnerability, with high rates of illiteracy, precarious basic sanitation conditions, high rates of teenage pregnancy and cesarean deliveries, infant mortality and low birth weight rates in significant proportion, and inefficient supply of information systems. Conclusion: An increase in the maternal mortality rate, the percentage of teenage pregnancy, and in the number of low birth weight infants and cesarean deliveries has been verified.